2018
DOI: 10.3176/tr.2018.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Ethnicity-Based Stigmatisation: The Case of Russian-Speaking Women in Estonia

Abstract: This article examines how ethnic minorities negotiate ethnicity-based boundaries and deal with stigmatisation. This is exemplified by the case of the Russianspeaking women in Estonia. To arrive at a more comprehensive understanding of expressions of ethnicity and responses to stigmatisation, we follow an intersectional approach, considering how constructions of ethnicity and reactions to stigmatisation are gendered. This study adds a gender dimension to understanding belonging and the discursive construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Although in this case the rationalisation offered can be regarded as a means of legitimising appearance-based discriminatory behaviour within the organisation, the undervaluation of the demand for legality in the situation is likely to have been based on the normalisation of unethical practices embedded in societal-level institutionalisation (Ojasoo, 2016). This interpretation is further supported by other research findings, which indicate that Estonian employers tend to be unaware of the legislation prohibiting discrimination during the recruitment process (Aavik et al. , 2020; Täht, 2019; Turk et al.…”
Section: Analysis and Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although in this case the rationalisation offered can be regarded as a means of legitimising appearance-based discriminatory behaviour within the organisation, the undervaluation of the demand for legality in the situation is likely to have been based on the normalisation of unethical practices embedded in societal-level institutionalisation (Ojasoo, 2016). This interpretation is further supported by other research findings, which indicate that Estonian employers tend to be unaware of the legislation prohibiting discrimination during the recruitment process (Aavik et al. , 2020; Täht, 2019; Turk et al.…”
Section: Analysis and Discussionsupporting
confidence: 76%
“…, 2015). Furthermore, awareness of the role and impact of stereotypes related to, for example, appearance in the recruitment process is low and employers tend not to use measures to reduce discrimination in the process (Aavik et al. , 2020; Täht, 2019).…”
Section: Context Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be noted that, in Europe, feminist scholarship has been focused on Roma women (Kóczé and Popa, 2009;Vincze, 2014), but scant attention and scholarly debate has addressed the gender-based differences among sub-state minorities (Kymlicka, 2007), who, due to political turbulence and the border changes mainly of the twentieth century, became ethnic minorities in Europe. One piece of research about sub-state ethnic minority women was undertaken in Estonia by Aavik (2015), who investigated the positions of Russian-speaking women on the labor market in Estonia. Aavik found that the awareness of ethnic belonging of the latter was much stronger than their gender awareness, and that they occupied the lowest paid positions on the Estonian labor market.…”
Section: Intersectionality As a Theoretical Frameworkmentioning
confidence: 99%
“…This more frequent highlighting of issues connected to race/ethnicity and gender (Brown and Gershon, 2017) suggests an awareness of intersectional identities. Other studies imply that ethnic minority women are more aware of their ethnic identity than their gender (Aavik, 2015;Morrison et al, 1987).…”
Section: Introductionmentioning
confidence: 99%